The Ellis Trail to Nicodemus: Revealing Stories in the Landscape of Black Westward Settlement - Discovery Phase Design Plan - Wigfall, La Barbara James; Kingery-Page, Katie (Mary Catherine); Wiersma, Erin R.; Epps, Kristen; Bates, Angela; Alexander, Robert (My University, 2024)
Nicodemus, Kansas, is the longest continuously inhabited, Black townsite west of the Mississippi River. The townsite of Nicodemus remains today as home to approximately twenty-four persons, who act as stewards of their historical legacy with support from thousands of former residents and descendants of the families of those freed people who settled in Nicodemus in the 1870s. Nicodemus represents the achievements of a group of formerly enslaved people who entered the West to experience freedom, autonomy, and homesteading through the establishment of their own town. The Nicodemus Historical Society & Museum’s (executive director, Angela Bates) original research has deepened understanding of the Ellis Trail to Nicodemus, a foot path and separate wagon trail used by newcomers to Nicodemus traversing the rolling grassland bluffs from the Ellis train station to their new home thirty-five miles away. The Nicodemus Historical Society & Museum has pieced together the trail route through painstaking research of recorded oral histories, photographs, and new interviews with descendants of Nicodemus settlers and white settlers along the Trail route. During the two-year National Endowment of the Humanities, Discovery Phase project, Nicodemus Historical Society & Museum worked with faculty members at Kansas State University and other humanities and digital media advisers to reveal this little-known aspect of Nicodemus’s history. This project interprets the cultural landscape of the Ellis Trail, a now invisible route winding through mid-grass prairie, down wooded riparian ravines, and along limestone bluffs; the wagon trail is sometimes visible as traces and sometimes now replaced by roadways. The product of this project is a thorough design plan for the digital product, an interactive website for viewers (a broad online audience ranging from middle school youth to adults) to understand the journey the first Nicodemus settlers took by wagon and on foot to the townsite. The website’s pages will also be connected to the physical landscape with an auto-tour along the Ellis Trail route, using smart codes to offer in-depth information about the settlers’ experience and the landscape’s hidden narrative. This Design Plan focuses upon specific humanities themes to be included, the visual and audio-visual assets to include, and a thorough site map for the website.
Keywords: Nicodemus KS; cultural landscapes; Kansas history; Ellis Trail to Nicodemus; African-American history